Penentuan Kadar Astaxanthin, Uji Antiinflamasi Dan Sitotoksik Terhadap Sel Kanker Payudara Ekstrak Aseton Spirulina Platensis - Armaini; Syafrizayanti; Zara Aulia (Departemen Kimia Universitas Andalas, 2022)
Spirulina platensis is a microalgae widely used in the health sector due to its micronutrients, biopigment such as astaxanthin. Astaxanthin is carotenoid belonging to strong antioxidant, which has anti-inflammatory and cytotoxic effects on MCF-7 breast cancer cells. This study aims to determine astaxanthin contents, to investigate the anti-inflammatory activity and cytotoxic potential of breast cancer cells MCF-7 treated with acetone extract from Spirulina platensis. Extraction is done by maceration method. Astaxanthin contents were determined using UV-Vis spectrophotometer set to 479 nm. The anti-inflammatory assays were performed using inhibition of protein denaturation method and cytotoxic assays were performed using the MTT method. From results of study, the extract contained 6,3008 mg/L astaxanthin. The IC50 values for anti-inflammatory and cytotoxic tests ​​were 363,399 mg/L and 66,68 mg/L, respectively. According to the result of the tests, acetone extract from Spirulina platensis showed anti-inflammatory activity and moderate cytotoxic activity against MCF-7 breast cancer cells.